Biomechanical Comparison of Fibertape Augmentation with Intercuneiform Adjunct and Cannulated Screws for Ligamentous Lisfranc Injuries: 3D Visualization of Complex Movement. Issue 1 (January 2022) - Koroneos, Zachary; Manto, Kristen M.; Martinazzi, Brandon; Stauch, Chris M.; Bifano, Shawn M.; Pace, Gregory I.; Lewis, Gregory; Aynardi, Michael C.
Category: Midfoot/Forefoot; Sports; Trauma Introduction/Purpose: The preferred method of fixation for ligamentous Lisfranc injuries is controversial, with the traditional method being transarticular screws. Unfortunately screw removal is often required leading surgeons to seek alternative fixation methods including fibertape constructs. Our lab has published biomechanical results on the safety and efficacy of a fibertape construct for the treatment of ligamentous Lisfranc injuries demonstrating biomechanical superiority with the supplementation of an intercuneiform limb. The purpose of this biomechanical study is to compare transarticular screws to a fibertape construct under loading and utilizing 3D visualization software. Methods: Three matched pairs of cadaveric specimens were dissected to allow for the placement of three screws on the dorsal aspect of the each bone involved in the Lisfranc complex. The diastasis between bones were measured at three midfoot joints in the Lisfranc articulation while each specimen was loaded to 75% of donor bodyweight. Measurements were obtained for the pre- injured specimens. The MC-2MT joint was sectioned under fluoroscopic imaging and re-measured to produce at least 2 mm of gapping. Specimens were then fixed with either transarticular screws or fibertape with an intercuneiform limb and computed tomography scans were performed. Post-fixation measurements were obtained for 250 N of axial loading with subsequent 100 N increases up to 650 N. CT scans were imported as DICOM images and the three bones were segmented to analyze the gapping that occurred at the dorsal, interosseous, and plantar portions of the ligament. Results: There were no significant differences detected for the diastasis between bones in the Lisfranc complex between the fibertape and screws. After loading to 650 N, no specimens had reached a diastasis of 2 mm through coordinate digitized measurements (Figure 1A and B). At 650 N of loading the fibertape specimens displayed an average diastasis of 0.78 mm while the specimens fixed with screws also displayed an average diastasis of 0.78 mm. 3D diastasis measurements showed coordinate digitized measurements were within 0.2 mm of those measured from 3D reconstruction of CT scans. The largest diastasis occurred at the dorsal aspect of the ligament. Conclusion: The use of a fibertape device involving a supplementary intercuneiform limb appears to provide a biomechanically viable alternative to screws for ligamentous Lisfranc injuries. Diastasis was verified using 3D computer models. Future efforts involve increasing the number of specimens, applying cyclic loading, and determining the effects on each portion of the ligament for each fixation type.